Association of CD4CD25FoxP3 regulatory T cells with natural course of childhood chronic immune thrombocytopenic purpura - Bo Ra Son; Ji Yoon Kim (Korean Pediatric Society, 2015)
PurposeThe purpose of this study was to determine the frequency of CD4+CD25+FoxP3+ regulatory T cells (Treg) in the peripheral blood of patients with childhood chronic immune thrombocytopenic purpura (ITP) exhibiting thrombocytopenia and spontaneous remission. The findings of this study indicate the possibility of predicting spontaneous recovery and pathogenesis of childhood chronic ITP.MethodsEleven children with chronic ITP (seven thrombocytopenic and four spontaneous remission cases; mean age, 8.8 years; range, 1.7-14.9 years) were enrolled in this study. Five healthy children and eight healthy adults were included as controls. The frequency of Treg was evaluated by flow cytometry in the peripheral blood.ResultsIn this study, four patients (36%) achieved spontaneous remission within 2.8 years (mean year; range, 1.0-4.4 years). The frequency of Treg was significantly lower in patients with persisting thrombocytopenia (0.13%±0.09%, P<0.05), than that in the patients with spontaneous remission (0.30%±0.02%), healthy adults controls (0.55%±0.44%), and healthy children controls (0.46%±0.26%). A significantly positive correlation was found between the frequency of Treg and the platelet count in children.ConclusionThese data suggest that a lower frequency of Treg contributes to the breakdown of self-tolerance, and may form the basis for future development of specific immunomodulatory therapies. Furthermore, Treg frequency has prognostic implication toward the natural course and long-term outcomes of childhood chronic ITP.